2017
DOI: 10.1007/s10562-017-2233-z
|View full text |Cite
|
Sign up to set email alerts
|

Ir-Catalysed Nitrous oxide (N2O) Decomposition: Effect of Ir Particle Size and Metal–Support Interactions

Abstract: The effect of the morphology of Ir particles supported on γ-Al2O3, 8mol%Y2O3-stabilized ZrO2 (YSZ), 10mol%Gd2O3-doped CeO2 (GDC) and 80wt%Al2O3-10wt%CeO2-10wt%ZrO2 (ACZ) on their stability on oxidative conditions, the associated metal-support interactions and activity for catalytic decomposition of N2O has been studied. Supports with intermediate or high oxygen ion lability (GDC and ACZ) effectively stabilized Ir nanoparticles against sintering, in striking contrast to supports offering negligible or low oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 25 publications
4
38
0
Order By: Relevance
“…On the basis of literature, pure CeO 2 exhibits two reduction peaks at 450 and 900°C (the latter being out of the sampled interval). The addition of gadolinium stabilizes cerium towards reduction, so that no signal is measured below 500°C as ceria reduction initiates above that temperature [14]. This is confirmed also by our measurements, reported in Figure 4: no important reduction events were observed for CGO below 900°C testifying its remarkable stability under reducing conditions.…”
Section: Tprsupporting
confidence: 88%
“…On the basis of literature, pure CeO 2 exhibits two reduction peaks at 450 and 900°C (the latter being out of the sampled interval). The addition of gadolinium stabilizes cerium towards reduction, so that no signal is measured below 500°C as ceria reduction initiates above that temperature [14]. This is confirmed also by our measurements, reported in Figure 4: no important reduction events were observed for CGO below 900°C testifying its remarkable stability under reducing conditions.…”
Section: Tprsupporting
confidence: 88%
“…Nagai et al have shown that the sintering of Pt in oxidizing conditions can be inhibited as a result of an increase of the electron density of oxygen in the support, which result in strong Pt‐oxide‐support interactions. It has also been proposed that oxygen spillover from the support to noble metal NPs can prevent NP agglomeration by introducing short‐range interparticle repulsion forces . High oxygen partial pressures, by increasing the surface density of surface oxygen, could therefore increase the Pt/TiO 2 adhesion energy and promote interparticle repulsion via enhanced oxygen spillover.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen ion lability (or lack of it) characteristic of these materials is related to their O 2mobility and oxygen storage capacity, which determine their propensity to provide spillover oxygen to metal particles dispersed on their surfaces [56][57][58][59][60]. This property can strongly modify the intrinsic catalytic activity of metal nanoparticles [56][57][58][59][60] and the investigation of such effects in the context of Rh-catalyzed DRM is the main objective of the present investigation. Catalytic measurements were carried out over a wide range of conditions over well-characterized samples and supplemented by state of the art XPS measurements involving in situ sample transfer between reaction cell and spectrometer chamber, without exposure to laboratory air.…”
Section: Ch4+ Co2 ⇋ 2co + 2h2mentioning
confidence: 99%
“…According to the double-layer account of promotion and metal-support interactions [56][57][58][59][60]78,80], oxygen back-spillover provides an effective double layer [O δ-, δ + ] (with δ≈ 2 [80]) on the Rh particles ( Fig. 10), altering their work function and chemisorptive properties and hence their intrinsic activity towards catalytic reactions [56][57][58][59][60]78,80].…”
Section: Mechanistic Implicationsmentioning
confidence: 99%